Adding mint extract to yoghurt - Fatima Martoub Mohsen Abdel Reda; Hussein sohail najem abod; Zahraa Chafat Jassim Hammadi; Aaya Muhammed Saied Almahdy; Noor Ali Hussein Obaid (Genius Journals, 2024)
Milk is one of the most important foods that accompanies a person from his birth until his old age. Milk, yogurt and their derivatives. We all need to drink milk, which is considered a complete food that provides us with calcium and many nutritional elements. We have researched this by making yoghurt, where dry milk of an amazing type was used. We also made yoghurt flavored with mint. 0And knowing the difference between the two models 0As a sensory evaluation of the models was conducted by professors and students of the Department of Food Science and the results of the evaluation were that there was no significant difference between the two models and for all characteristics 0From this it became clear that adding mint to milk does not affect its characteristics but rather gives it a different appearance and adds nutritional value and flavor to it. Desirable
Keywords: Mint extract; yoghurt; milk